Perspectives on the Application of Unmanned Aircraft for Freshwater Fisheries Census. Issue 11 (23rd November 2018) - Tyler, S.; Jensen, O. P.; Hogan, Z.; Chandra, S.; Galland, L. M.; Simmons, J.; ,
Abstract : This work provides an overview of the use of small unmanned aircraft systems for freshwater fisheries survey and fish identification. As an example, a series of river reaches in Mongolia was surveyed for identification and sizing of the endangered Taimen Hucho taimen, the world's largest salmonid. Using polarized video imagery, Taimen were positively identified in depths of over 2 m. River reaches were chosen for survey to include likely Taimen holding grounds as well as areas that were unlikely Taimen habitat. Large areas of river reaches were quickly surveyed with video imagery stored for analysis. Using land‐based targets for sizing and flying autonomous search patterns, we found that Taimen were easily identifiable based on their swimming patterns and could be remotely sized; furthermore, the fish did not appear to be disturbed by the presence of overhead aircraft. Lessons learned from the experiments and recommendations for future advances are provided. The use of small unmanned aircraft systems for fisheries is shown to be a novel and inexpensive alternative to traditional fisheries survey methods.